Solve the differential equation 2y'''+ y''- 8y' - 4y = 7 - 2e-x - cos2 (2x).
Let
y=yh+yp
To find the homogeneous equitation,
An auxillary equation is
"2m^3+m^2-8m-4=0"
"2m^2(m+1)-4(2m+1)=0"
"(2m^2-4)(m+1)=0"
"(m+2)(m-2)(2m+1)=0"
"m=2,-2 ,-\\frac 12"
Hence ,the homogeneous solution is
"y_h=C_1e^{\\frac{-x}{2}}+C_2e^{-2x}+C_3e^{2x}"
To find the particular solution,
By trigonometric identities;
"7-2e^{-x}-cos^2(2x)=7-2e^{-x}-\\frac12-\\frac12cos(4x)=\\frac{13}2-2e^{-x}-\\frac12cos(4x)"
Now,
Let
"y_p=A+Be^{-x}+Ccos(4x)+Dsin(4x)"
By differentiation;
"y_p'=-Be^{-x}-4Csin(4x)+4Dsin(4x)"
"y_p''=Be^{-x}-16Ccos(4x)-16Dsin(4x)"
"y_p'''=-Be^{-x}+64Csin(4x)-64Dcos(4x)"
By substitution into the given equation;
"-2Be^{-x}+128Csin(4x)-128Dcos(4x)+Be^{-x}-16Ccos(4x)-16Dsin(4x)+8Be^{-x}+32Csin(4x)-32Dcos(4x)-4A-4Be^{-x}-4Ccos(4x)-4Dsin(4x)=\\frac{13}2-2e^{-x}-\\frac12cos(4x)"
Simplify;
"-4A+3Be^{-x}+(160C-20D)sin(4x)+(-160D-20C)cos(4x)=\\frac{13}2-2e^{-x}-\\frac12cos(4x)"
By comparison;
"-4A=\\frac{13}2"
"A=-\\frac{13}8"
"3B=-2"
"B=-\\frac23"
"(160C-20D)=0"
"C=\\frac18D" ....(i)
Also,
"-160D-20C=-\\frac12" ...(ii)
Combining (i) and (ii) ,
"D=\\frac {1}{325}"
"C=\\frac{1}{2600}"
Substitute the constants into yp;
"y_p=-\\frac{13}8-\\frac23e^{-x}+\\frac1{2600}cos(4x)+\\frac1{325}sin(4x)"
Hence the general solution of the question is
"y=y_h+y_p"
"y=C_1e^{-\\frac x2}+C_2e^{-2x}+C_3e^{2x}-\\frac{13}2-\\frac23e^{-x}+\\frac{1}{2600}cos(4x)+\\frac1{325}sin(4x)"
Comments
Leave a comment